Dosage calculations made incredibly easy! - Harvey, Margaret, 1952- (Philadelphia : Wolters Kluwer Health, 2016)
Calculate correct dosages with safety and confidence, with the easy-to-follow nursing expertise of Dosage Calculations Made Incredibly Easy! 5th edition. This fully illustrated guide offers the complete how-to on calculating dosages for all drug forms and administration routes, with numerous practice exercises and seasoned guidance on interpreting drug orders accurately. Understand class materials more fully, get ready for the NCLEX or certification exam, or refresh your calculationNCLEX or certification exam, or refresh your calculation skills with this enjoyable text
Includes bibliographical references and index
1 13
Keywords: drug dosage calculations; Drugs -- Dosage; Pharmaceutical arithmetic; Pharmaceutical Preparations -- administration & dosage